2021
DOI: 10.1128/mbio.00065-21
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 ORF6 Disrupts Bidirectional Nucleocytoplasmic Transport through Interactions with Rae1 and Nup98

Abstract: RNA viruses that replicate in the cytoplasm often disrupt nucleocytoplasmic transport to preferentially translate their own transcripts and prevent host antiviral responses. The Sarbecovirus accessory protein ORF6 has previously been shown to be a major inhibitor of interferon production in both severe acute respiratory syndrome coronavirus (SARS-CoV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here, we show SARS-CoV-2-infected cells display an elevated level of nuclear mRNA accumulation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
114
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 48 publications
11
114
1
Order By: Relevance
“…A deletion of 27 a.a, which maps to a putative signal peptide within the ORF7a protein, has recently been reported in two SARS-CoV-2 isolates from two separate patients (Holland et al, 2020). This large deletion of the ORF7a is proposed to prevent redundant functions on inhibition of cellular protein synthesis also found associated with the ORF6 protein that, as we have seen above, interacts with the mRNA export proteins NUP98 and RAE1 and may inhibit cellular translation (Addetia et al, 2020(Addetia et al, , 2021. The a.a sequence of the SARS-COV-2 ORF7a protein is very close to the ORF7a of bat-SL-CoV-RaTG13 ORF7a like that of the Pangolin-CoV-2019, but much more distant than that of the bat-SL- 97.5,and 40% a.a identity,respectively).…”
Section: Orf 7a and Orf 7b Proteinsmentioning
confidence: 55%
See 1 more Smart Citation
“…A deletion of 27 a.a, which maps to a putative signal peptide within the ORF7a protein, has recently been reported in two SARS-CoV-2 isolates from two separate patients (Holland et al, 2020). This large deletion of the ORF7a is proposed to prevent redundant functions on inhibition of cellular protein synthesis also found associated with the ORF6 protein that, as we have seen above, interacts with the mRNA export proteins NUP98 and RAE1 and may inhibit cellular translation (Addetia et al, 2020(Addetia et al, , 2021. The a.a sequence of the SARS-COV-2 ORF7a protein is very close to the ORF7a of bat-SL-CoV-RaTG13 ORF7a like that of the Pangolin-CoV-2019, but much more distant than that of the bat-SL- 97.5,and 40% a.a identity,respectively).…”
Section: Orf 7a and Orf 7b Proteinsmentioning
confidence: 55%
“…However, an upregulation of several genes, all involved in the NF-kB pathway, was noted after infection with these variants in comparison to the reference strain, suggesting that the truncated ORF6 proteins could play a role in the inflammatory host-response (Xia et al, 2020). Lately, the SARS-CoV-2 ORF6 protein function as a potent IFN antagonist (Yuen et al, 2020;Kimura et al, 2021) and also was found to block nuclear import of a wide range of host factors through interactions with RAE1 and NUP98 (Addetia et al, 2021).…”
Section: Orf6 Proteinmentioning
confidence: 99%
“…The associations suggested by these PPI analyses need to be validated by further experiments. To date, only Orf6 has been shown to interrupt the host nucleocytoplasmic trafficking [75][76][77][78] and to induce an aberrant distribution of Nups (Nup98 and Rae1) [76]. Xia et al found that Orf6 binds to importin-α1 to block the nuclear translocation of IRF3, resulting in an impaired type I IFN production in the HEK293T cell line [78].…”
Section: Mechanisms Of the Host Nuclear Transport Machinery Hijacking By Virusesmentioning
confidence: 99%
“…Nevertheless, these α-importins may not be the direct key players because their overexpression failed to rescue an Orf6-dependent blockade of green fluorescent protein (GFP)-tagged STAT1 nuclear import. Interestingly, Addetia et al reported that the SARS-CoV-2 Orf6 interactions with Nup98 and Rae1 were much stronger than those of SARS-CoV-1 Orf6, suggesting the strong IFN antagonism triggered by SARS-CoV-2 contributes to the high prevalence of asymptomatic cases of SARS-CoV-2 infection [77].…”
Section: Mechanisms Of the Host Nuclear Transport Machinery Hijacking By Virusesmentioning
confidence: 99%
See 1 more Smart Citation